Strategi BUMDesa Ketapanrame “Mutiara Welirang” Berbasis Thinking Ahead Dalam Mengembangkan Desa Wisata - Sri Roekminiati, Sri Roekminiati; Supranoto, Supranoto; Panca Oktawirani, Panca Oktawirani (International Conference on Multidisciplinary Issues (INCOMI), 2024)
This article aims to describe and analyze the strategy carried out by BUMDesa Ketapanrame "Mutiara Welirang" to develop the Ketapanrame tourist village. The focus of this research is the development of dynamic governance-based tourist villages, especially dynamic thinking ahead capabilities. Starting from culture, natural charm, community participation, networking, infrastructure and other supports to realizing Tourism Village. These strategies are: 1. Village Asset Management for 5 (five) business units, namely: 1) Village Drinking Water Management Unit, Cleanliness Management Unit, 3) Kiosk and Livestock Stall Unit, 4) Tourism Management Unit, and 5) Capital and Partnership. 2. Exploring and developing village potential by implementing a collaboration strategy between all stakeholders: 1) Government, 2) Private sector, 3) Community, 4) Academics, and 5) Media. 3. Develop community involvement in BUMDesa businesses. Community involvement in BUMDesa businesses by 2023 will be 1022 heads of families or 53.47% of the 1,911 heads of families in Ketapanrame village.